Is there a linkage between sustainable development and market access of LDCs? - Tania, Sharmin Jahan (© 2013 Law and Development Review, 2016)
This article was published in the Law and Development Review [© 2013 Law and Development Review] and the definite version is available at : http://doi.org/10.1515/ldr-2013-0005 The Journal's website is at: https://www.degruyter.com/view/j/ldr.2013.6.issue-1/ldr-2013-0005/ldr-2013-0005.xml